Reconstruction intramedullary nailing for a failed subtrochanteric Seinsheimer type IIB fracture: a case report - Wang, Fei; Liu, Tianfeng; Guo, Shoujin; Wu, Lei; Xin, Peiwang (Frontiers in Surgery, 2023)
Introduction: A case of subtrochanteric Seinsheimer ⅡB fracture was retrospectively analyzed to determine the causes of failure and the possible problems with femoral reconstruction intramedullary nailing. Methods: This study focused on a case of an elderly patient with Seinsheimer type IIB fracture treated with minimally invasive femoral reconstruction intramedullary nailing. By retrospectively analyzing the intraoperative and postoperative course, we can identify the reasons for that may lead to this deficiency and avoid similar problems in the future. Result: It was observed that the nail was dislodged after surgery, and the broken end was displaced again. Through analysis and research, we believe that non-anatomical reduction, deviation of needle insertion point, improper selection of surgical methods, mechanical and biomechanical effects, doctor–patient communication and non-die-cutting cooperation, and non-compliance with doctor’s orders may be related to the success of surgery. Conclusion: Femoral reconstruction intramedullary nailing is used for the treatment of subtrochanteric Seinsheimer ⅡB fractures; however, non-anatomical reduction, choice of needle insertion point, inappropriate choice of surgical method, mechanical and biomechanical effects, doctor–patient communication and cooperation without die-cutting, and non-compliance with doctor’s advice may result in surgical failure. According to the analysis of individuals, under the premise of accurate needle entry point, minimally invasive closed reduction PFNA or open reduction of broken ends and intramedullary nail ligation for femoral reconstruction can be used in Seinsheimer type IIB fractures. It can effectively avoid the instability of reduction and the insufficiency of the biomechanics caused by osteoporosis.